113k views
0 votes
Which one is the correct answer?

Which one is the correct answer?-example-1

1 Answer

6 votes

Answer:

C

Explanation:

So I'm going to subtract (x+7)/(x+3) on both sides:

(x-6)/(x+5)-(x+7)/(x+3)>=0

Now I'm going to find a common denominator which is (x+5)(x+3).

[(x-6)(x+3)-(x+7)(x+5)]/[(x+5)(x+3)]>=0

Now I just have a lot of simplifying to do:

[x^2+3x-6x-18-(x^2+5x+7x+35)]/(x^2+3x+5x+15)>=0

[-3x-18-12x-35]/(x^2+8x+15)>=0

[-15x-53]/[x^2+8x+15]>=0

User Mehran Hatami
by
6.3k points